Dr. Hackney STA Solutions pg 61

# Dr. Hackney STA Solutions pg 61 - Second Edition 4-17 Then...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Second Edition 4-17 Then the Jacobian is J= z1 x1 z2 x z1 y z2 y = bY D -aY D -bX D aX D = aY bX 1 1 aX bY - = = , D2 D2 D - 1-2 X Y and we have that fX,Y (x, y) = = 1 -1 2 e 2 (2X Y x - X X (Y (x-X )+X (y-Y ))2 2(1+) 2 2 X Y 1 -1 2 e 2 (Y (x-X )+X (y-Y ))2 2(1-) 2 2 X Y 1 1-2 X Y 1 - 2 )-1 exp - y - Y Y + 1 2(1 - 2 ) 2 x - X X 2 - 2 y - Y Y , - < x < , - < y < , a bivariate normal pdf. d. Another solution is aX aY cX cY = = = = X bX = Y bY = 0 X Y . (1 - 2 )X 2 2 There are an infinite number of solutions. Write bX = X -a2 ,bY = Y -a2 , and X Y substitute bX ,bY into aX aY = X Y . We get 2 aX aY + X -a2 X 2 Y -a2 Y = X Y . Square both sides and simplify to get 2 2 2 2 (1 - 2 )X Y = X a2 - 2X Y aX aY + Y a2 . Y X This is an ellipse for = 1, a line for = 1. In either case there are an infinite number of points satisfying the equations. 4.47 a. By definition of Z, for z < 0, P (Z z) = = = = = = P (X P (X P (X P (X P (X P (X z and XY > 0) + P (-X z and XY < 0) z and Y < 0) + P (X -z and Y < 0) (since z < 0) z)P (Y < 0) + P (X -z)P (Y < 0) (independence) z)P (Y < 0) + P (X z)P (Y > 0) (symmetry of Xand Y ) z)(P (Y < 0) + P (Y > 0)) z). By a similar argument, for z > 0, we get P (Z > z) = P (X > z), and hence, P (Z z) = P (X z). Thus, Z X n(0, 1). b. By definition of Z, Z > 0 either (i)X < 0 and Y > 0 or (ii)X > 0 and Y > 0. So Z and Y always have the same sign, hence they cannot be bivariate normal. ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online